Religious Authority in Islamic Law: A Debate on Conservative and Progressive Methods - Alif Rizky Ramadhan; Ai Fatimah Nur Fuad (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2023)
There are two major competing groups in Islamic jurisprudence, the first is the value-laden scholars’ group who believe that religious authority comes from conservative and collective understanding and the second is the value-free scholars’ group who believe that religious authority comes from progressive and individual understanding. These two groups have contested over the highest authority between collective ijtihad and individual ijtihad in producing Fiqh products. This article aims to discuss a discourse on the contestation between value-laden and value-free. This research is conducted through qualitative method based on case studies. It is also focus on literature review of various primary and secondary sources. We identified and selected many relevant sources that linked very closely to both the substance of the topic as well as to the theories that we used to strengthen the research’s arguments, data analysis, and findings. However, Kuntowijoyo’s theory ‘Islam as Science’ is used as the main tool to construct a new and neutral authority. As a result, this research offers the middle way of Fiqh that can bridge the two major groups, as well as can be used as an alternative discourse to construct a new, moderate, and neutral meaning.